Geochronology of the late Pleistocene catastrophic Biya debris flow and the Lake Teletskoye formation, Altai Region, Southern Siberia. Issue 14 (25th October 2016) - Baryshnikov, Gennady; Panin, Andrei; Adamiec, Grzegorz
ABSTRACT: In the Biya River valley flowing from Lake Teletskoye, geomorphic and sedimentological evidence of a catastrophic debris flow has been found and assigned to glacier retreat after the last glacial maximum. Here, we report the results of lithological analysis of three sedimentary sections along Lake Teletskoye–the Biya River valley system and optically stimulated luminescence dating of key stratigraphic units that led to a revised model for the geomorphic history of the region. Maximal glacier advance is suggested to have occurred during MIS 4–early MIS 3. It was accompanied by the damming of tributary valleys by ice, by terminal and side moraines, and by the accelerated aggradation of the trunk valley below the glacier front. Formation of Lake Teletskoye, which followed the glacier retreat, occurred between 35 and 40 ka BP, most probably around 37.5 ka BP. Lake formation was shortly followed by a break in the moraine dam, catastrophic debris flow, rapid valley incision, and reduction in the lake level by ~100 m. Subsequently, incision has proceeded at a much lower rate and produced valley deepening and lake lowering of 30–35 m in the last 35–40 ka, or 0.8–0.9 m per thousand years on average.